Fundamentação pós-metafísica do direito e da democracia na concepção de J. Habermas - Salvetti, Ésio Francisco (2011)
Our work aims to reflect on the post-metaphysical foundation of law and democracy. Forthis, we will face problems such as: language, reason, metaphysics, pluralism, complexity, characteristics of contemporary society. To fulfill the objective we have considered the philosopher Jürgen Habermas. Study the fundamentals post-metaphysical of Law and Democracy implies fundamentally resume the theoretical foundations of Habermas' philosophy evaluating his position theses modern and postmodern, causing the bridge to the implications of that plea. The biggest challenge faced is finding founding principles of social cohesion without resorting to metaphysical and religious principles that traditionally establish and legitimate. In this sense, Habermas goes beyond the metaphysical tradition and influenced by the yaw-linguistic posits language as an effective means for social cohesion, characterized, so as post-metaphysical. In a further step, we will seek to extend the principle of discourse about the validity of rights and democracy. For Habermas characterizes itself as a democratic and legitimate. Through the democratic process of legitimation of rights, where everyone can understand them, it is addressed and authors' rights, we understand that the possibility of maintenance of pluralism and social complexity. In this sense, we noted the possibility of a cohesive society with a post-metaphysical.